Значення белігеративних ландшафтів у формуванні історико-культурної спадщини України - Антонюк, О. О.; Antoniuk, O. O. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Розглянуто роль та значення белігеративних ландшафтів у формуванні історико-культурної спадщини України, шляхи їх оптимізації та включення у перелік заповідних об’єктів. The article is devoted to the role and importance of the fortification landscapes in forming historical and cultural heritage of Ukraine, ways of their optimization and the inclusion in the list of the protected sites.
Importance of the Fortification Landscapes in Forming Historical and Cultural Heritage of Ukraine
Keywords: белігеративні ландшафти; історико-культурна спадщина; заповідання; туристичні ресурси; fortification landscapes; historical and cultural heritage; protection; travel resources